INTERCONNECTEDNESS BETWEEN SPEECH ACTS' EXPRESSIONS AND SPEAKERS' SOCIAL VARIABLE: A Comparative Study of Female Main Character in Expressing Feeling of Dislike in Two Chicklist - Husnun Nisa, - (2007)
This study is designed to look at the comparison between two main characters in communicating their feeling of dislike. The data for this study were obtained from the expressions uttered by the main characters in the two popular genres of feminism novel so-called chicldits. The chicldits are 'Sttt... Im A Playgirl by Sari Azis and 'Fmny Feeling' by Dilla Rosa. Inspired by the principle of the descriptive qualitative method, the expressions were categorized into five speech acts' classes and were analyzed by means of the theory of level of directness. The parameter used to measure the level of directness of an utterance was related to the characters' social variables; educational background and occupation. It is found that both main characters show differences in choosing strategies. The first tends to directly threaten hearer by using expressive speech acts most ofthe time whereas the second is indirect and more sarcastic by using directives speech acts. Having critically discussed the findings, the present study concludes that social variables influence one's linguistics behavior. Therefore, it strengthens the claim of linguists who argue that both matters are related one to the other